Radiocarbon measurements of small-size Foraminiferal samples with the Mini Carbon Dating System (MICADAS) at the University of Bern: implications for paleoclimate reconstructions - Gottschalk, Julia; Lippold, Jörg (Radiocarbon, 2018)
Radiocarbon (14C) measurements of foraminifera often provide the only absolute age constraints in marine sediments. However, they are often challenging as their reliability and accuracy can be compromised by reduced availability of adequate sample material. New analytical advances using the MIni CArbon DAting System (MICADAS) allow 14C dating of very small samples, circumventing size limitations inherent to conventional 14C measurements with accelerator mass spectrometry (AMS). Here we use foraminiferal samples and carbonate standard material to assess the reproducibility and precision of MICADAS 14C analyses, quantify contamination biases, and determine foraminiferal 14C blank levels. The reproducibility of conventional 14C ages for our planktic (benthic) foraminiferal samples from gas measurements is 200 (130) yr, and has good precision as illustrated by the agreement between both standards and their reference values as well as between small gas- and larger graphitized foraminiferal samples (within 100±60 yr). We observe a constant contamination bias and slightly higher 14C blanks for foraminifera than for carbonate reference materials, limiting gas (graphite) 14C age determinations for foraminifera from our study sites to ~38 (~42) kyr. Our findings underline the significance of MICADAS gas analyses for 14C on smaller-than-conventional sized foraminiferal samples for paleoclimate reconstructions and dating.
Gesehen am 14.05.2019